Opimalizace typů, granulometrie a tvaru jemných částic pro speciální betony - Jobánek, Jaromír (Vysoké učení technické v Brně. Fakulta stavební, 2019)
Tato diplomová práce je zaměřena na optimalizaci křivky zrnitosti použitím příměsí. K návrhu betonu výborných vlastností je často třeba dosáhnout vyšší hutnosti směsi, a to pomocí návrhu vhodné křivky zrnitosti. Také jsou v práci popisovány betony speciálních vlastností a různé druhy příměsí.

This diploma thesis is focused on optimization of particle size distribution using concrete additions. To design a concrete of excellent properties, it is often necessary to achieve a higher packing density of the mixture by designing a suitable particle size distribution curve. Concrete with special properties and various types of powder additions are also described.
Optimization of types, granulometry and fine particle shape for special concrete
Keywords: optimalizace; granulometrie; jemné částice; příměsi; pórovitost; tvar zrn; hutnost; křivka zrnitosti; optimization; granulometry; fine particles; additions; porosity; grain shape; density; particle size distribution